Żydzi i kwestia żydowska w prozie niefikcjonalnej Zinaidy Gippius - Krycka-Michnowska, Iwona (Rusycystyczne Studia Literaturoznawcze, 2017)
In this paper the views of Zinaida Gippius on the status, place and role of the Jews in history, expressed in the diaries, journalistic writing and essays were analysed. A reading of these texts leads to the conclusion that the writer had an ambivalent attitude to the Jews. On the one hand, her position, especially soon after the Bolshevik revolution, corresponding to negative stereotypes, but on the other hand overcome it. The journalistic writing and Gippius’ diaries comes belief in the need for reconciliation and in the possibility of achieving it. The hope for a harmonious coexistence of people connects Gippius with religious movements in Russia, the revival of the Orthodox Church and the opening of the Jews to Christianity.